2021
DOI: 10.1016/j.isci.2021.103131
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of non-neutralizing antibodies and interferon-γ for cross-protection against influenza

Abstract: Summary Current influenza vaccines do not typically confer cross-protection against antigenically mismatched strains. To develop vaccines conferring broader cross-protection, recent evidence indicates the crucial role of both cross-reactive antibodies and viral-specific CD4 + T cells; however, the precise mechanism of cross-protection is unclear. Furthermore, adjuvants that can efficiently induce cross-protective CD4 + T cells have not been identified. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…While much of vaccine development focuses on neutralizing antibody activity, it is becoming appreciated that nonneutralizing antibodies also can play a role in an effective immune response against viruses such as influenza (46)(47)(48)(49)(50). A number of studies have indicated the role of cross-reactive nonneutralizing antibodies in providing cross-protection against antigenically divergent heterologous influenza viral strains (47, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…While much of vaccine development focuses on neutralizing antibody activity, it is becoming appreciated that nonneutralizing antibodies also can play a role in an effective immune response against viruses such as influenza (46)(47)(48)(49)(50). A number of studies have indicated the role of cross-reactive nonneutralizing antibodies in providing cross-protection against antigenically divergent heterologous influenza viral strains (47, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells subsets, which orchestrate the immune response and help prime B cells during infection ( Chen et al., 2020a ), performed a more significant proliferation ( Figures 3 G and 3H). It was worth mentioning that interferon-gamma (IFN-γ), produced primarily by activated natural killer cells, Th1 cells, and CD8 + cytotoxic cells, is a pivotal moderator of cellular immunity to fight multiple pathogens ( Shibuya et al., 2021 ). The percentages of IFN-γ-secreting cells in both CD4 + and CD8 + T cells subsets in mice primed with HMVs were notably higher than that in mice treated with PBS ( Figures 3 I and 3J), suggesting that HMVs could modulate IFN-γ-mediated immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…The extensive antibody range induced by the adjuvanted PNP hydrogel platform against varied strains and subtypes, poorly immunogenic NA antigens, as well as historically difficult HA antigen regions is evidence that sustained delivery can increase the diversity and potency of humoral responses to influenza vaccination [20] . A breadth of anti-HA antibodies is known to be protective against infection by the virus [18, 72] and furthermore increases the chance of gaining immunity that will be maintained against future mutations. The ease of use of our adjuvanted PNP hydrogel system, shown in this work to readily admix with commercial Fluzone, provides a promising way to “supercharge” current influenza vaccination infrastructure to better protect our global populations against both annual influenza and pandemic risks.…”
Section: Discussionmentioning
confidence: 99%